Exotic Diseases of Citrus Identification Sheet - Megan M. Dewdney; Jamie D. Yates; Michael E. Rogers; Timothy M. Spann (EDIS)
PP264, a 2-page ID sheet by M.M. Dewdney, J.D. Yates, M.E. Rogers, and T.M. Spann, provides images for identification and a comparison chart for Citrus Variegated Chlorosis (CVC), Leprosis, Citrus Black Spot, Sweet Orange Scab (SOS), and Citrus Tristeza Stem-Pitting (CTV-SP). Published by the UF Department of Plant Pathology, April 2009.